The effect of designing an interactive e-book on learning engagement for sixth graders with learning disabilities - Al-Otaibi, Hessah Abdullah; Ismail, AbdelRaouf Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to measure the impact of the design of an interactive electronic book on the development of engaging in learning among sixth -grade primary students with learning difficulties in Riyadh. the researcher used the semi-experimental curriculum with the experimental design of one group in the tribal and post applications, and the study sample was chosen in the way of the intention of students with difficulty learning in the sixth grade of primary school 276 primary school of the educational administration in Riyadh, which reached (10) students, the researcher used the scale of engaging in learning as ameasurement tool that represented the treatment of current study problem. after treating the grades of female students in the pre-applications of the pre-applications of the scale of engaging in three main axes: academic challenge, participation and interaction, and educational satisfaction includes the following dimensions:(behavioral learning involvement), (cognitive learning involvement), (emotional learning involvement). is with the aim of developing the level of engaging in learning among members of the study sample using the interactive e-book in study unit for the course of my language for the sixth grade of primary school. the study concluded that there is difference between the average students, grades of the study in learning in perspective of the use of experimental processing material represented in designing an interactive electronic book, in light of the study results, the researcher recommended number of recommendations that urge the importance of interactive e-books design in teaching learning topics on other categories and decisions.